1989
DOI: 10.1128/aem.55.12.3143-3149.1989
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial sorption of heavy metals

Abstract: Four bacteria, Bacillus cereus, B. subtilis, Escherichia coli, and Pseudomonas aeruginosa, were examined for the ability to remove Ag+, Cd2+, Cu2+, and La3+ from solution by batch equilibration methods. Cd and Cu sorption over the concentration range 0.001 to 1 mM was described by Freundlich isotherms. At 1 mM concentrations of both Cd2+ and Cu2+, P. aeruginosa and B. cereus were the most and least efficient at metal removal, respectively. Freundlich K constants indicated that E. coli was most efficient at Cd2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
101
1
4

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 443 publications
(112 citation statements)
references
References 29 publications
4
101
1
4
Order By: Relevance
“…The uptake of dissolved iron on the surfaces of microorganisms is well known (Mullen et al 1989). Konhauser et al ( 1993) have reported that metallic ions of solute-rich fluviatile waters become bound to the acidic polysaccharide capsules of bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The uptake of dissolved iron on the surfaces of microorganisms is well known (Mullen et al 1989). Konhauser et al ( 1993) have reported that metallic ions of solute-rich fluviatile waters become bound to the acidic polysaccharide capsules of bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Biosorption is a process which represents a cost-effective, as well as an ecofriendly, tool for removing heavy metals using biological material (Gadd, 2009). Several microbial sources, such as algae (Filip et al, 1979), bacteria (Mullen et al, 1989), yeast (Machado et al, 2008), and fungi (Kapoor et al, 1999) have been used by scientists across the world for biosorption experiments. Among the various microbial populations, bacterial biomass has been found to be the most significant in metal biosorption, and hence, the use of bacteria for removal/detoxification of heavy metals has received considerable attention in recent years (Oves et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial cell walls can adsorb a wide range of aqueous metal cations, potentially altering the mobility of the metals in geologic systems (e.g., Beveridge & Murray, 1976, 1980Beveridge & Koval, 1981;Crist et al ., 1981;Harvey & Leckie, 1985;Goncalves et al ., 1987). Most previous studies of bacterial surface adsorption have involved bacterial cells that were not metabolically active during the period of adsorption, focusing on the passive binding that occurs between bacterial surface functional groups and aqueous metal cations (e.g., Mullen et al ., 1989;Fein et al ., 1997;Haas et al ., 2001;Ngwenya et al ., 2003). Metal cations appear to bind predominantly to deprotonated sites within the bacterial cell wall.…”
Section: Introductionmentioning
confidence: 99%